Empowering frail elderly people : opportunities and impediments in housing, health, and support service delivery - Heumann, Leonard; McCall, Mary E., 1960-; Boldy, Duncan (Praeger, 2001)
An analysis of provider-, environment-, client- and societal-based obstacles to the empowerment of frail elderly persons in a philosophical framework of social values. It features international case studies which provide examples of the feasibility of achieving real empowerment.